2000
DOI: 10.1029/1999gl002356
|View full text |Cite
|
Sign up to set email alerts
|

Slow variations in mean path of the Gulf Stream east of Cape Hatteras

Abstract: Abstract.The continually leak from the current into the Slope Sea. These observations point to a thermohaline rather than winddriven mechanism for governing the path of the Gulf Stream after it leaves the coast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
69
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 12 publications
13
69
1
Order By: Relevance
“…1a, where the cold SST anomalies south of the Grand Banks, observed 2 years prior, have been replaced by warm SSTs in the range of 0.28-1.08C, suggesting a northward shift of the GSNW. Warm anomalies in the slope sea were attributed by Rossby and Benway (2000) to a reduction of cold water flux from the Labrador shelf, consistent with the warm temperature anomalies south of the Grand Banks in Fig. 1b.…”
Section: Sst Response To Il Variationssupporting
confidence: 63%
“…1a, where the cold SST anomalies south of the Grand Banks, observed 2 years prior, have been replaced by warm SSTs in the range of 0.28-1.08C, suggesting a northward shift of the GSNW. Warm anomalies in the slope sea were attributed by Rossby and Benway (2000) to a reduction of cold water flux from the Labrador shelf, consistent with the warm temperature anomalies south of the Grand Banks in Fig. 1b.…”
Section: Sst Response To Il Variationssupporting
confidence: 63%
“…The positive correlation, indicating that warming (cooling) is associated with northward (southward) shifts of the Gulf Stream, is significant (at the 90% significance level) for lags ranging from -12 to +2 months. The negative sense of the lag means that SST changes precede shifts of the GS path, as was found by other authors (Rossby (1999) and Rossby and Benway (2000)). As the lag advances, the patch of high correlation gradually spreads from the eastern side of the domain towards the Gulf Stream/DWBC cross-over point.…”
Section: Stream Pc1 Lag-correlationsupporting
confidence: 60%
“…Rossby (1999) and Rossby and Benway (2000) found that fluctuations in the Gulf Stream position correlate with changes in the surface temperature and salinity changes in the Slope-Shelf region. Before the Gulf Stream shifts north, the Slope-Shelf surface temperature rises.…”
Section: Stream Pc1 Lag-correlationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Peñ a-Molino and Joyce (2008) found that the essentially barotropic slope currents near 708W lead the GS shifts by 6 months and suggested that an increased DWBC transport indeed precedes a southward GS shift. Nonlinearity, eddy dynamics, and other factors may also influence the GS position, such as the entrainment of the upper core of the DWBC (Spall 1996) and changes in the Labrador Sea shelf transport (Rossby and Benway 2000).…”
Section: Relation Between the Gulf Stream And The Mocmentioning
confidence: 99%